التداخل التطبيقي بين المصلحة المرسلة والاستحسان عند الحنفية في المعاملات المالية = Interference of application between maṣlaḥah mursalah and Istiḥsān of the Hanafi School in business transaction = Pertindihan aplikasi di antara maṣlaḥah mursalah dan istiḥsān dalam Mazhab Hanafi dalam transaksi kewangan - Hossain, Farhat; Ghalia, Bouhedda (IIUM Press, International Islamic University Malaysia, 2018)
المصلحة المرسلة والاستحسان دليلان مهمان من الأدلة الشرعية المختلف فيها التي تعتني بالمسائل الاجتهادية للحُ كم على المستحدثات، وقد وقع الاختلاف بين المذاهب في حجيتهما، وكذا كثُرت الآراء في احتجاج الحنفية بالمصلحة المرسلة بخاصة، ومن ثم ركَّز الباحث على كشف التداخل بين المصلحة المرسلة والاستحسان بجمع ما أمكن من أقوال الحنفية وآرائهم فيها، ودراستها دراسة تحليلية؛ لبيان حقيقة هذا التداخل عندهم في التطبيقات، وقد نُوقش هذا التداخل التطبيقي بين المصلحة المرسلة والاستحسان عند الحنفية في المعاملات المالية في مجالات: الاستصناع، والمضاربة، والضمان، ومن أهم النتائج التي توصَّل إليها الباحث ثبوت المصلحة المرسلة عند الحنفية في صورة الاستحسان بالتداخل بينهما في التطبيقات. ********************************************************* Maṣlaḥah mursalah (unrestricted public interest) and istiḥsān (juristic preference) are considered among two vital evidences of Islamic jurisprudence and important principles of ruling on new issues that are subject to ijtihād (juristic reasoning). However, the disagreement that occurred among the schools of Islamic law on the authenticity of maṣlaḥah mursalah and istiḥsān as evidences in the Sharīʿah. In some mazhab, such as the Ḥanafī school, maṣlaḥah mursalah was used extensively for deriving rulings of Sharīʿah. At this very juncture, this research focuses on gathering opinions within Ḥanafī school regarding the overlappings between maṣlaḥah mursalah and istiḥsān, studying them in order to understand the views and interpretations of Ḥanafī school for it. In term of application this research discusses the interference in the field of business transaction, specifically for sectors such as istiṣnāʿ, muḍārabah and ḍamān. This study is an analytical approach in order to achieve the real meaning behind the interference between these two evidences in application level. The major findings of the study include considering maṣlaḥah mursalah by the Ḥanafī school as an evidence for deriving ruling of the Sharīʿah in the form of istiḥsān by showing the interference between them in term of applications. ******************************************************** Maslahah Mursalah dan Istihsan dikira sebagai prinsip penting dalam membuat hukum baru yang memerlukan ijtihad. Perselisihan pendapat berlaku di antara para ulama sama ada dua hukum ini sama ada boleh diterima atau tidak sebagai sumber hukum. Malah terdapat perselisihan pendapat dikalangan ulama mazhab Hanafi juga untuk menerima keduanya untuk membuat hukum Shariah atau tidak. Kajian ini akan berfokus untuk mengumpulkan pendapat-pendapat dalam Mazhad Hanafi dan mengkajinya untuk memahami pandangan dan tafsiran mazhab Hanafi terhadap perkara ini. Dari sudut aplikasi, kajian ini akan membincangkan penggunaan dua hukum ini dalam transaksi kewangan terutamanya dalam: istiṣnāʿ, muḍārabah and ḍamān. Kajian akan mengunakan analisis untuk mencapai makna sebenar disebalik penggunaan hukum ini dari sudut aplikasinya. Dapatan terpenting dalam kajian termasuk untuk menerima Maslahah Mursalah dalam bentuk Istihsan kerana pertindihan keduanya semasa mengaplisakikannya.